Can We Determine Osteoarthritis Severity Based on Systemic Immuno-Inflammatory Index? - Bilge Kagan Yilmaz; Recep Altin; Alper Sari (Diagnostics)
Background: Osteoarthritis (OA) is one of the common joint diseases. Hematologic markers have been investigated to determine its severity and predict the prognosis of joint diseases. In this study, we investigated whether the systemic immune-inflammatory index (SII) is a marker for assessing the severity of OA. Methods: The records of patients diagnosed with OA at various stages between 1 January 2020 and 1 January 2022 were retrospectively analyzed. Patients aged 18–75 years with complete blood count within the last 15 days and not taking anti-inflammatory drugs were included in the study. Patients were classified according to the Kellgren–Lawrance classification as stage 1-2-3 mild to moderate OA (Group I) and stage 4 severe OA (Group II). A total of 1580 patients were diagnosed with knee OA and 946 were included in the study. Of the patients, 246 (26%) were male and 700 (74%) were female. The mean age of the patients was 61.00 (53.00–68.00) years. Results: There were 449 (47.5%) patients in Group I and 497 (52.5%) patients in Group II. Statistically significant differences were found between the groups in age, gender, hemoglobin, lymphocytes, and SII (p < 0.05). An SII value of 627.9 was found to distinguish severe OA from mild–moderate OA with 42.5% sensitivity and 70.6% specificity. Conclusions: Although this study is the first in the literature, it shows that SII has limited predictive value in assessing the severity of knee OA. Future research should focus on longitudinal studies to establish causality and explore therapeutic implications.